Demographic origins of the decline in labor's share - Andrew Glover; Jacob Short (Bank of Canada, 2023)
Since 1980, the earnings share of older workers has risen in the United States. At the same time, labor's share of income has declined significantly. We hypothesize that an aging workforce has contributed to the decline in labor's share of income. We formalize this hypothesis in an on-the-job search model in which employers of older workers may have substantial monopsony power due to the decline in labor market dynamism that accompanies aging. The greater monopsony power manifests as a growing wedge between a worker's earnings and their marginal product over the life cycle. We estimate the profile of these wedges using cross-industry variation in labor's share and the age distribution of earnings. We find that a 60-year-old worker receives half the marginal product relative to when they were 20. Together with recent demographic trends, this can account for 59% of the recent decline in labor's share of earnings in the United States.
Keywords: D33; E25; J1; J3; J62; 330; Labour markets; Productivity